A wolf in sheep's clothing? Patients' and healthcare professionals' perceptions of oxygen therapy: An interpretative phenomenological analysis. (13th November 2016) - Kelly, Carol A.; Lynes, Dave; O'Brien, Mary R.; Shaw, Ben
Abstract: Background: Despite emerging evidence and guidelines, poor prescribing and administration of oxygen therapy persists. This study aimed to explore healthcare professionals' (HCPs) and patients' perceptions of oxygen. Design: Semi‐structured interviews with 28 patients and 34 HCPs. Findings: Three master themes uncovered: oxygen as a panacea, the burden of oxygen and antecedents to beliefs . Patients used oxygen for breathlessness and as an enabler; they were grateful to oxygen and accepted it as part of the disease. HCPs used oxygen because it helps patients; it works; and it makes HCPs feel better. But oxygen is not benign and a burden is evident with potential antecedents to beliefs revealed. Summary: The findings suggest that a set of fixed beliefs regarding oxygen exist, influenced by several impacting factors. The perception that oxygen is a universal remedy presides, but is, at times, contradictory. These findings will raise awareness of entrenched cultures, influence future educational and research strategies, and inform policy.